High resolution STEM/EDX spectral imaging to resolve metal distributions within ∼100 nm combustion generated ash particles. Issue 7 (3rd July 2019) - Wang, Yueming; Van Devener, Brian; Li, Xiaolong; Wendt, Jost O. L.
Abstract: Ultrafine ash particles play an important role in establishing a sticky inner deposit layer on heat transfer surface for power plants, but it is still unclear whether a thin surface alkali coating on these ultrafine particles might control this deposition behavior. In this research, we used a high resolution FE-TEM/STEM equipped with twin SDD EDX detectors for high X-ray detection efficiency, to determine the presence and absence of surface enrichment of alkali metals on ultrafine solid fuel ash samples that had low bulk alkali compositions but high deposition rates. Results from two types of combustion generated nano-sized ash particles are presented. One was from the oxy-combustion of pulverized bituminous coal, the other from oxy-combustion of pulverized rice husks, both being burned in a 100 kW rated down-flow laboratory combustor. Elemental mapping results from STEM/EDX uncovered some surface enrichment of alkali metals in ultrafine ash particles, where it existed, as it did for combustion of rice husks. However, it was not able to discern similar alkali metal surface enrichment for the bituminous coal ultrafines that had resulted in even higher deposition rates. Since deposition rates from both of these cases lie on the same correlation with PM1, one can conclude that although surface enrichment of alkali metals is present for some ∼100 nm particles, it is not a prerequisite to achieve high inner surface deposition rates. This is in contrast to prevailing theories that point to alkali metals as "bad actors" as far as the sticky inner deposition rate is concerned. Copyright © 2019 American Association for Aerosol Research